Long-Term Outcomes of Peripheral Blood Mononuclear Cells in the Treatment of Angiitis-Induced No-Option Critical Limb-Threatening Ischemia - Jiang, Xiaolang; Liu, Hao; Pan, Tianyue; Gu, Shiyang; Fang, Yuan; Wei, Zheng; Fang, Gang; Chen, Bin; Jiang, Junhao; Shi, Yun; Liu, Peng; Fu, Weiguo; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Peripheral blood mononuclear cells (PBMNCs) showed encouraging short outcomes in the treatment of angiitis-induced no-option critical limb-threatening ischemia (AICLTI) in the pilot study. This study aimed to demonstrate the long-term outcomes of this treatment. Methods: From May 2014 to December 2018, patients diagnosed with AICLTI and treated by autotransplantation of PBMNCs in our center were enrolled and analyzed. The primary endpoint was major amputation-free survival (MAFS), the secondary endpoints included peak pain-free walking time (PPFWT), Wong-Baker FACES pain rating scale score (WFPRSS), labor recovery, ankle-brachial index (ABI), transcutaneous partial oxygen pressure (TcpO2), and SF-36v2 scores. Results: A total of 58 patients were enrolled. During a minimal follow-up of 36 months, the MAFS was 93.1% and the labor competence restored rate was 62.1%. The WFPRSS was decreased from 8.7 ± 1.6 to 1.6 ± 3.2, and PPFWT was significantly improved from 2.9 ± 4.2 min to 16.6 ± 6.9 min. The quality of life was also significantly improved at each follow-up point. Perfusion evaluating parameters, such as ABI and TcPO2, were also significantly improved. No critical adverse event was observed during the treatment and follow-up period. Conclusions: The treatment of AICLTI by autotransplantation of PBMNCs demonstrated encouraging long-term results. It could not only restore labor competence, improve the quality of life, but also significantly reduce the major amputation rate.